Communication interculturelle à l’hôpital: réflexion autour de la médiation - Graber, Myriam (My University, 2002)
This article aims at a better understanding of the communication between care-givers and migrant patients in relation to several services (medicine, surgery, obstetrics, geriatrics and psychiatry). Efficiency of different communication strategies is examined through the analysis of interviews. Among these strategies, the practical and theoretical issues of the cultural mediation are particularly focused and linked to a reflection on several common representations about discourse (opacity vs. transparency).